2010
DOI: 10.1016/j.thromres.2009.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Detection of endogenous tissue factor levels in plasma using the calibrated automated thrombogram assay

Abstract: SummaryBackground-The calibrated automated thrombogram (CAT) assay measures thrombin generation in plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
57
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 47 publications
9
57
0
1
Order By: Relevance
“…During this step, known as the propagation phase, 10 TF becomes less important, because the reaction is mainly driven by the FVIIa/FXa and FVa/FXa complexes. 18,24 To further understand to what extent tumor cell TF contributes to thrombin generation, two different strategies were used: (i) inhibiting cell-associated TF with a specific anti-TF antibody, and (ii) performing the assay in FVIIdeficient plasma. In both cases, the thrombin generation NB4 K562 HEL H69 MCF7 NB4 K562 HEL H69 MCF7 NB4 K562 HEL H69 MCF7 NB4 K562 HEL H69 MCF7 NB4 K562 HEL H69 MCF7 NB4 K562 HEL H69 MCF7 NB4 K562 HEL H69 MCF7 NB4 K562 HEL © F e r r a t a S t o r t i F o u n d a t i o n capacity of all cell lines was significantly reduced, and the decrease was proportional to cell TF content.…”
Section: Discussionmentioning
confidence: 99%
“…During this step, known as the propagation phase, 10 TF becomes less important, because the reaction is mainly driven by the FVIIa/FXa and FVa/FXa complexes. 18,24 To further understand to what extent tumor cell TF contributes to thrombin generation, two different strategies were used: (i) inhibiting cell-associated TF with a specific anti-TF antibody, and (ii) performing the assay in FVIIdeficient plasma. In both cases, the thrombin generation NB4 K562 HEL H69 MCF7 NB4 K562 HEL H69 MCF7 NB4 K562 HEL H69 MCF7 NB4 K562 HEL H69 MCF7 NB4 K562 HEL H69 MCF7 NB4 K562 HEL H69 MCF7 NB4 K562 HEL H69 MCF7 NB4 K562 HEL © F e r r a t a S t o r t i F o u n d a t i o n capacity of all cell lines was significantly reduced, and the decrease was proportional to cell TF content.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies may recognize ''encrypted'' nonfunctional TF or degraded forms of TF protein that are not active, leading to poor correlation between levels of TF-protein and TF activity (13). Osterud and Bjorklid suggested that antibodies do not meet the stringent criteria of monospecificity (26), this may explain the discrepancy between TF activity and TF protein.…”
Section: Discussionmentioning
confidence: 99%
“…TF-positive MPs can be analyzed by immunological assays [flow cytometry, impedance flow cytometry, and enzyme-linked immunosorbent assay (ELISA)] or functional assays (FXa-generating activity, thrombin generation assay, and clot formation assay), (10,11,(13)(14)(15). Some reports have demonstrated discrepancies between TF-protein and TF activity levels, which have been explained by antibody binding to ''encrypted'' or degraded forms of inactive TF-protein (13,16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent publications have highlighted how low-grade contact activation is greatly amplified by the presence of phospholipids simulating the procoagulant membranes of activated platelets. 7,8 Thus, the dramatic effects on recalcification times observed with preactivation of platelets in their study 2 likely stem from platelet-dependent amplification of material-induced contact activation and not from FXIIa generation by platelets per se. In Figure 1B, we show that the Amelung instrument they used 2 generates far more FXIIa than comparable assays.…”
mentioning
confidence: 81%